Animal Objects: Memory, Desire and Mourning - Julia Courtney (Cahiers Victoriens et Edouardiens)
My article examines the ways in which animal bodies have been transformed into objects charged with powerful affective forces, arranging the discussion under the themes of memory, desire and mourning. Hunting trophies, taxidermic mounts and domestic objects made from preserved dismembered parts, allowed retired colonial ‘Nimrods’ and intrepid ‘Dianas’ to relive the vivid experiences of big game hunting. At the same time disembodied claws, teeth and horns carried an erotic charge when transformed into lovers’ gifts, while the sensuous reaction to animal skins can be seen in contemporary art and fiction. Thirdly, mourning for departed pets or celebrity animals, in an age when death and remembrance were significant cultural forces, might involve the preservation of either a whole animal or isolated body parts, as in the case of larger creatures such as horses. Drawing on contemporary journalism, fiction and descriptions of the objects themselves, I examine topics including the irony of ‘naturalisation’, the synecdoche of dismembered parts, and the power of objects to focus emotions. While the death of the animal is implicit in the construction of the domestic object, possession of the object allows the owner to recapture, even to re-experience, intensely lived moments of danger, violence, comradeship, physical prowess, closeness to nature and, especially, of power.